2002
DOI: 10.1021/jp026577f
|View full text |Cite
|
Sign up to set email alerts
|

New Density Functional and Atoms in Molecules Method of Computing Relative pKaValues in Solution

Abstract: A theoretical structure−property relation between pK a and Bader's atoms in molecules (AIM) energy of the dissociating proton was obtained by an approximation of the standard gas-phase expression for the equilibrium constant expressed in terms of molecular partition functions. This relation was then tested by solvated density functional computations on a series of aliphatic carboxylic acids, substituted benzoic acids, phenols, anilinium ions, and pyridinium ions using the COSMO solvation model. Comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
148
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 56 publications
9
148
3
Order By: Relevance
“…All the calculated pK a values at HF/6-311þþg(d,p) levels lead to very large error compared with the experimental data. Although Adam [17] thinks that carboxylic acid requires two water molecules to make an accurate pK a prediction, we suggest that an accurate pK a prediction requires three water molecules, which can be verified by Table III. To analyze the structure of the clusters (of Fig.…”
Section: Resultssupporting
confidence: 52%
“…All the calculated pK a values at HF/6-311þþg(d,p) levels lead to very large error compared with the experimental data. Although Adam [17] thinks that carboxylic acid requires two water molecules to make an accurate pK a prediction, we suggest that an accurate pK a prediction requires three water molecules, which can be verified by Table III. To analyze the structure of the clusters (of Fig.…”
Section: Resultssupporting
confidence: 52%
“…Accordingly, many researchers are tending to calculation of pKa values using theoretical and computational approaches. 21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Recently quantum chemical calculations, using thermodynamical parameters such as Gibbs free energy, have reported good correlations between calculated and experimental acidities of a wide range of organic and inorganic acids. 18,[42][43][44][45][46][47][48][49][50] For example, gas phase and solution phase acidities of some organic compounds investigated by Namazian et al and Kheirjou et al reported good correlation between ab initio calculations of pKa values with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…A good theoretical description of these reaction mechanisms therefore depends on the ability to predict accurately the solution pK a of the reacting functional groups. Several protocols for computational determination of pK a have been developed by several authors [1][2][3][4][5][6]. They all rely on the determination of gas-phase reaction energies, followed by computation of solvation energies of the basic and acidic forms of the molecular species under study using implicit solvent models [1][2][3]5,6] or the Poisson equation [4], in the presence [2,3,5,6] or absence [1,4,6] of a few explicit water molecules.…”
Section: Introductionmentioning
confidence: 99%